PERBANDINGAN SIRIRAJ SKOR (SS) DAN ALGORITMA GAJAH MADA (AGM) KASUS STROKE DI IGD RSUD Dr. SOEDONO MADIUN - Saudin, Didik; Rajin, Mukhamad; Kriswanto3, Yadi (Jurnal EDUNursing, 2020)
Abstract               Stroke is a neurological disorder and cerebrovascular disease where the highest mortality rate is in Indonesia. The purpose of this study is to compare the neurological assessment method for Siriraj Score (SS) with the Gajah Mada Algorithm (AGM) at the service level in the Emergency Room (IGD) in order to accelerate further action. The method used in this study is the SPSS T-Test to see the SS and AGM significance and the correlation test between them using Pearson. The result of SS has a probability of α = 0.000 or <0.05 means that SS has a strong relationship, while in AGM the probability value α = 0.000 <0.05 means that it also has a relationship in determining the stroke diagnosis. The result of the significance level between siriraj and Gajah mada is 0.812> 0.05, which means that there is no relationship between SS and AGM. The importance of fast and precise assistance to all stroke patients in order to avoid delays in help avoiding disability and death of the nurse's skills need to increase knowledge with an easy examination application implemented in the Emergency Room Service.  Keyword: Stroke, Siriraj Score, Gajah Mada Algorithm.